Dekonstruksi Hukum Social Commerce Indonesia : Perspektif Demokrasi Ekonomi di Era Digitalisasi - Aditya Prastian Supriyadi (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2024)
Social commerce (S-Commerce) comes from the disruption of business digitalizationthat explores social media. When s-commerce was developing, Indonesia bannedthe platform because it was considered to kill local businesses and capitalize onthe market. The decision can potentially contradict economic democracy in oneof the provisions of Article 33, paragraph (4) of the 1945 Constitution, whichopens up technological space for developing the national economy. The purposeof writing this article is to deconstruct economic democracy on commercial lawon social media as a Government policy that prohibits S-Commerce. The writingarticle uses normative legal research methods with statutory, legal comparison, andconceptual approaches. There are two research results in this article. First, at a timewhen significant nations are embracing technology at a rapid pace to boost theirbusinesses, the government's decision to outlaw s-commerce has negatively impactedthe nation. Based on the doctrine of digitalization, economic law is not appropriate ifit has to ban S-Commerce. The business paradigm of the contemporary era must beintegrated with technology to compete with the development of the digital economy inthe global realm. Second, based on economic democracy in Article 33, paragraph (4)of the 1945 Constitution, S-Commerce manifests a national economy balanced withtechnological progress by the constitution's mandate. S-Commerce law provisionsneed to be deconstructed using the principles of economic democracy. So, reasonablelegislative parameters may promote the growth of the digital economy while notjeopardizing the local economy.